2002
DOI: 10.1111/1464-0597.00081
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Structural Relation of Personal Efficacy to Collective Efficacy

Abstract: Dans cette recherche, on éprouve un modèle structurel concernant l'impact du statut socioéconomique sur l'efficacité individuelle perçue et le rapport qu'elle entretient avec la perception de l'efficacité collective. Dans les travaux sociodémographiques, les jeunes, par comparaison aux plus âgés, s'estiment moins efficaces dans la gestion de leur vie professionnelle, de leurs relations intimes et de leur situation financière, mais plus aptes à promouvoir le changement social. Les hommes ont plus que les femmes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
121
1
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(147 citation statements)
references
References 52 publications
7
121
1
7
Order By: Relevance
“…www.efsupit.ro 293 Knowledge and abilities) and collaborate toward a shared goal (Fernandez-Ballesteros et al, 2002). However, this study confirmed that the perceived collective efficacy had a positive impact on group effectiveness and performance and that collective efficacy played a mediating role between bridging social capital and value cocreation.…”
Section: Jpes ®mentioning
confidence: 51%
See 2 more Smart Citations
“…www.efsupit.ro 293 Knowledge and abilities) and collaborate toward a shared goal (Fernandez-Ballesteros et al, 2002). However, this study confirmed that the perceived collective efficacy had a positive impact on group effectiveness and performance and that collective efficacy played a mediating role between bridging social capital and value cocreation.…”
Section: Jpes ®mentioning
confidence: 51%
“…Self-efficacy is considered the basis of human agency (Fernandez-Ballesteros, Diez-Nicolas, Caprara, Barbaranelli & Bandura, 2002). While self-efficacy represents a person's belief in his or her ability to perform a task and influence events, a lot of research has been conducted about how individuals feel, think, motivate themselves, and act; self-efficacy also facilitates goal setting, investment, and persistence (Ahmad & Safaria, 2013;Armitage, Conner, Loach & Willetts, 1999;Bandura, 1993Bandura, , 1994Hackett & Betz, 1981;Scholz, Gutierrez-Dona, Sud & Schwarzer, 2002;Schwarzer & Fuchs, 1995).…”
Section: Collective Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…The meaning that Bandura puts into concept of self-efficacy, which he places at the center of social cognitive theory, stands out in this context in explaining the mutual dependency between personal agency and social structure. In a sense, social cognitive theory and the concept of perceived self-efficacy should be regarded as a rejection of any dualism between social structures and personal subject (Ballesteros, Nicolá s, Caprara, Barbaranelli & Bandura, 2002). In this respect, self-efficacy should be interpreted as a construct derived from social cognitive theory, which assumes human behavior, cognition and environment shape each other dynamically through mutual triple causal effect (Gist & Mitchell, 1992).…”
Section: Concept Of Self-efficacymentioning
confidence: 99%
“…Bandura explains this view with the example of children in authoritarian education systems having less self-efficacy about taking responsibility of their own learning even though children in different countries have equal self-efficacy. Ballesteros et al (2002) points out that different types of perceived efficacy can differ according to age and gender. For example, although males and females do not differ in their perceived efficacy to manage their own lives, males have stronger perceived efficacy to change their lives for the better through social change.…”
Section: Concept Of Self-efficacymentioning
confidence: 99%